2005
DOI: 10.2135/cropsci2005.0639
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ancestral Lines of U.S. Soybean Cultivars for Resistance to Four Soybean Viruses

Abstract: Fifty‐two North American (NA) ancestral soybean [Glycine max (L.) Merr.] lines were screened for resistance to Bean pod mottle virus (BPMV), Soybean mosaic virus (SMV) strains G1 and G5, Tobacco ringspot virus (TRSV), and Tobacco streak virus (TSV). Seven ancestors, ‘CNS’, ‘Haberlandt’, ‘Ogden’, ‘Peking’, PI 71506, PI 88788, and ‘Tokyo’, were resistant to SMV‐G1. Sixteen entries, ‘A.K. (Harrow)’, ‘Capital’, CNS, FC 33243, Haberlandt, ‘Illini’, ‘Improved Pelican’, ‘Laredo’, ‘Lincoln’, ‘Mandarin’, ‘Mandarin (Ott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 51 publications
5
27
0
Order By: Relevance
“…The results from our screening of soybean germplasm agree with those of Wang et al (2005) who reported that 52 soybean ancestral lines were susceptible, having positive serological results with various degrees of mosaic and leaf distortion, to the inoculation with a subgroup I BPMV isolate. In another study, Zheng et al (2005) did not find resistance in 18 soybean genotypes screened but observed that the severity of mosaic symptoms varied among genotypes and BPMV isolates.…”
Section: Discussionsupporting
confidence: 90%
“…The results from our screening of soybean germplasm agree with those of Wang et al (2005) who reported that 52 soybean ancestral lines were susceptible, having positive serological results with various degrees of mosaic and leaf distortion, to the inoculation with a subgroup I BPMV isolate. In another study, Zheng et al (2005) did not find resistance in 18 soybean genotypes screened but observed that the severity of mosaic symptoms varied among genotypes and BPMV isolates.…”
Section: Discussionsupporting
confidence: 90%
“…Tobacco ringspot virus belongs to the Nepoviridae family (Stace-Smith, 1985) of the nepovirus group (Ross, 1987 Cobb)]. Transmission can also occur through infected seeds and mechanical inoculation (Bergson et al, 1964;Hill, 2003;Wang et al, 2005). Seed transmission and TRSV infection can be greater when plants are infected with the virus before fl owering (Athow and Bancroft, 1959;Demski and Harris, 1974).…”
Section: Reactions Of Mid-southern Us Soybean Cultivars To Bean Podmentioning
confidence: 99%
“…Due to diVerences in climate and soils each main production region can be further divided into smaller subregions (Wang 1991;Pan et al 1994;Wang and Gai 2002). Each region has diVerent growing conditions and locally adapted cultivars (Lu et al 1981;Bu and Pan 1987).…”
mentioning
confidence: 99%
“…The Chinese landraces have also been introduced into other major soybean-producing countries including the United States, Brazil, and Japan (Chang et al 1998). Disease resistant resources such as Peking and PI 88788 for soybean mosaic virus and soybean cyst nematode (Heterodera glycines Ichinohe) resistance have been used in the US for the development of new soybean cultivars (Pantalone et al 2003;Anand et al 2004;Wang et al 2005).…”
mentioning
confidence: 99%